Korelasi jenis dan lama waktu pemberian obat antituberkulosis paru terhadap kadar glukosa darah di RSUP Sanglah periode 2015-2016 - Gde Dicky Arimbawa; Ni Kadek Mulyantari (DiscoverSys Inc., 2019)
Background: Tuberculosis (TB) is a chronic infectious disease caused by an infection of the Mycobacterium tuberculosis complex. Antituberculosis (OAT) drugs used in TB treatment include Isoniazid (H), Rifampicin (R), Pyrazinamide (Z), Ethambutol (E), and Streptomycin (S). The effects of OAT use are many that are hepatotoxic. This hepatotoxic disrupts liver function as a very important glucose buffer system. The purpose of this study was to determine the correlation of the type and duration of administration of OAT to blood glucose levels at Sanglah Hospital.Method: This study is an analytical study with a cross sectional study design. The population in this study were tuberculosis patients who were treated at Sanglah General Hospital, Denpasar in March 2015 - October 2016. The selection of samples used consecutive sampling with a total sample of 38.Results: The correlation test results between the duration of OAT administration and blood glucose levels in tuberculosis patients at Sanglah General Hospital using the spearman test obtained a correlation coefficient (r) value of 0.536 so that according to statistics it can be concluded that there is a positive correlation between the length of time OAT is to blood glucose concentrations. The correlation test between the type of OAT on blood glucose levels in tuberculosis patients in Sanglah General Hospital used the chi-square test obtained P value is 0.133 so according to statistics it can be concluded that there was no significant relationship between the type of OAT to blood glucose concentrations in tuberculosis patients at Sanglah Hospital.Conclusion: There is a significant positive correlation between the duration of OAT treatment of blood sugar levels, but there is no relationship between the type of OAT to blood sugar levels in patients with pulmonary tuberculosis.